2017
DOI: 10.1021/acs.jpcc.7b04647
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation and Theoretical Modeling of Benzothiadiazole-Based Charge-Transfer Chromophores: From Solution to Nanoaggregates

Abstract: Experimental and theoretical investigations are presented on four quadrupolar molecules constituted of a central electron-acceptor 2,1,3-benzothiadiazole conjugated at both sides with electron-donating thiophene (or 2,2′-bithiophene) substituted groups. Previous investigation of their physicochemical properties demonstrated that thermally induced self-organization might be achieved for one of them. In this study, we further explore the structure−properties relationships for these quadrupolar chromophores also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 78 publications
6
45
0
Order By: Relevance
“…T1 compounds feature two main absorption bands: the most intense one is rather broad and spans the entire region between 450 and 650 nm, while the other one is found at about 400 nm. The spectra are reminiscent of those observed for T1 ‐dyes in solution (see Figure S1 for the comparison), where the two peaks were attributed to two CT transitions . However, focusing on the shape of the main band, we recognize a complex structure, made up of at least three distinct components, at approximately 500 nm, 530 nm (coinciding with the absolute maximum) and 575 nm, suggesting interesting effects of aggregation on the optical properties of the dyes.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…T1 compounds feature two main absorption bands: the most intense one is rather broad and spans the entire region between 450 and 650 nm, while the other one is found at about 400 nm. The spectra are reminiscent of those observed for T1 ‐dyes in solution (see Figure S1 for the comparison), where the two peaks were attributed to two CT transitions . However, focusing on the shape of the main band, we recognize a complex structure, made up of at least three distinct components, at approximately 500 nm, 530 nm (coinciding with the absolute maximum) and 575 nm, suggesting interesting effects of aggregation on the optical properties of the dyes.…”
Section: Resultssupporting
confidence: 50%
“…In previous works, we demonstrated that the high absorptivity of the dyes in a large portion of the visible region is barely affected by the terminal chains in solution, however an interesting differentiation is observed in the solid state, where T1CAO displays liquid crystalline behaviour ,. Moreover, these molecules are able to form stable organic nanoparticle suspensions (ONPs) in water, where the C 8 chains promote the partial self‐assembly into weakly fluorescent aggregates . Here, we further investigate the aggregation of these molecules in powders and spin‐coated films, exploring the effects and modifications of the optical properties induced by temperature and by mechanical grinding.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Essential-state models( ESMs)p rovide as imple and physically sound description of CT chromophores [54][55][56] and their aggregates, [57][58][59][60][61] and were effective in rationalizing the different propensityt os ymmetry breaking of various families of quadrupolar and octupolar dyes. [28,62,63] ESMsd escribe each dye in terms of am inimal set of basis states, corresponding to the main resonating structures.…”
Section: Essential-state Modelingmentioning
confidence: 99%
“…It has been interpreted on the basis of the excited-state symmetry breaking model induced by the solvent polarity: the first electronic excited state is characterized by the charge localization on one arm of the molecule, so that the emission originates from a polar state stabilized in polar solvents. We propose that this model, already used in order to explain the positive emission solvatochromism in V-shaped molecules, [58] can effectively apply to these pseudo-quadrupolar dithienosilole-based molecules.…”
Section: Optical and Photophysical Propertiesmentioning
confidence: 99%